A multi-objective robust possibilistic programming approach to designing sustainable and reliable closed-loop supply chain network (case study: aluminum industry) - Sajad Amirian; Maghsoud Amiri; Mohammad Taghi Taghavifard (تصمیم گیری و تحقیق در عملیات)
Purpose: In this research, a multi-product and multi-period closed-loop supply chain design problem with three objectives of profitability, social responsibility, and reliability under uncertain conditions has been considered.Methodology: Triangular fuzzy numbers have been used for non-deterministic parameters, and a robust probabilistic programming approach with the Me scale has been used to deal with fuzzy constraints. The proposed approach eliminates the need for iterative consideration by decision-makers by providing unlimited choices from the optimism-pessimism spectrum. The mathematical model developed in this research is of mixed integer linear programming type, which is implemented in GAMS software to solve it and find Pareto optimal solutions.Findings: The accuracy of the overall performance of the proposed model has been evaluated with four examples (based on the coefficients of the objective functions) from a case study in the aluminium industry. The sensitivity analysis of the demand parameter showed that the proposed model achieved more economic profit, less social responsibility, and less reliability with increasing demand.Originality/Value: The variability of the justified decision space in the Me criterion has helped to solve the supply chain network design problem more flexibly and closer to reality through the possibility of exchange between the objective function and the risk-taking level of the managers.